Trisiloxane-centred metal–organic frameworks and hydrogen bonded assemblies. Issue 32 (2nd August 2018) - Delmas, Luke C.; White, Andrew J. P.; Pugh, David; Horton, Peter N.; Coles, Simon J.; Lickiss, Paul D.; Davies, Robert P.
Abstract : A trisiloxane-centred hexacarboxylic acid linker has been synthesized and used in the preparation of new hybrid MOF materials. Abstract : A hexacarboxylic acid with a trisiloxane backbone (L -H6 ) has been prepared and applied in MOF construction.L -H6 itself crystallizes as an unusual 2D hydrogen-bonded network. Reaction ofL -H6 with Mn(ii ) gaveIMP-20 and with Zn(ii ) gaveIMP-21 : both are 3D MOFs incorporating Si–O–Si–O–Si linkages.